Prevalence of Haemoprotozoan Infection in Equines of Maharashtra - Pawar, Sanyogita S; Meshram, Milind D; Borikar, Sudhirkumar T; Khillare, Kavita P; Mote, Chandrashekhar S; Tumlam, Uma M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The prevalence of haemoprotozoan infection in equines was studied by screening 121 clinically suspected blood samples by PCR and  Giemsa stained method for the presence of Theileria equi, Babesia caballi and Trypanosoma evansi from the horses admitted at Veterinary  Clinical Complex of the college from Shirwal, Panchgani, Mahabaleshwar, and Baramati. Out of 121 horses, 12 (9.92%) were positive  for Theileria equi by PCR and 6 (4.95%) by microscopic examination and all horses were negative for B. caballi and T. evansi. The blood  smear examination technique was less sensitive (4.95%) when compared to PCR for the detection of T. equi infection. The highest area wise prevalence of T. equi infection was observed in Panchgani (12.90%) followed by VCC Shirwal (10.71%), Mahabaleshwar (8.82%),  and Baramati (7.14%). The prevalence of T. equi was recorded highest in the Marwari breed (15.79%) and horses of age group 2-18  years (12.5%). The highest prevalence of T. equi in horses was recorded in the month of May (33.33%). These findings can help make a  comprehensive control and preventive strategy of equine piroplasmosis in Maharashtra.
Keywords: Babesia caballi; Horse; Prevalence; Theileria equi; Trypanosoma evansi